Chiral Separation of Apremilast by Capillary Electrophoresis Using Succinyl-β-Cyclodextrin—Reversal of Enantiomer Elution Order by Cationic Capillary Coating - Zoltán-István Szabó; Beáta-Mária Benkő; Ágnes Bartalis-Fábián; Róbert Iványi; Erzsébet Varga; Levente Szőcs; Gergő Tóth (Molecules, 2023)
A stereospecific capillary electrophoresis method was developed for the separation of the novel, antipsoriatic agent, apremilast (APR). Six anionic cyclodextrin (CD) derivatives were screened for their ability to discriminate between the uncharged enantiomers. Only succinyl-β-CD (Succ-β-CD) presented chiral interactions; however, the enantiomer migration order (EMO) was unfavorable, and the eutomer, S-APR, migrated faster. Despite the optimization of all possible parameters (pH, cyclodextrin concentration, temperature, and degree of substitution of CD), the method was unsuccessful for purity control due to the low resolution and the unfavorable enantiomer migration order. Changing the direction of electroosmotic flow (EOF) by the dynamic coating of the inner surface of the capillary with poly(diallyldimethylammonium) chloride or polybrene resulted in EMO reversal, and the developed method could be applied for the determination of R-APR as the enantiomeric purity. Thus, the application of the dynamic capillary coating offers a general opportunity for enantiomeric migration order reversal in particular cases when the chiral selector is a weak acid.